Description of some Master's Theses in Mathematics Education - Salvador Hernández Vaca; Héctor Manuel Jacobo García (Universidad Autónoma de Baja California, 2011)
In this paper we present some operational indicators to assess the theses presented by graduates of the MA in Mathematics Education. The paper presents data from the theses by orientation, by thematic field, and by theoretical framework and methodological tools; and lists the authors most often cited. Using this information, we infer graduates' vision concerning mathematics education; their role as teachers; and the knowledge that various courses have left with them for their professional development. The question this research seeks to answer is: what theoretical framework and methodological tools did students working on their Master's Degree in Mathematics Education use to carry out their proposals for pedagogical intervention in their theses?